Pengaruh Media Pembelajaran Audio Visual Muatan IPA Subtema Benda Tunggal dan Campuran terhadap Hasil Belajar Siswa Kelas V MI Setia Bhakti Trawas - Agung Purwono; Widi Astuti (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2021)
Learning outcomesare the ultimate goal of implementing a learning activity at school. Learning outcomes can be improved through conscious efforts that are carried out systematically leading to positive changes whish are then called the learning process. Thuis audio visual learning media can affect student learning outcomes. Because this media can generate motivation, can make it easier for students to understand the material presented by the teacher, and stimulate learning activities. In this study examines the effect of audio-visual learning media which aims to improve student learning outcomes of class V MI Setia Bhakti Trawas, to determine the difference in student learning outcomes in classes that apply learning media with those who do not apply learning media as materials conveying aids. This research is a quantitative research with a quasi-experimental type using a design (two groups pretest posttest). In this study, the sample used was 25 students. The data collection technique is in the form of a test by using 10 essay questions, observation and documentation. Based on the findings of this study, the value of sig <0.05 is 0.000, it can be seen that the average value of student learning outcomes who have applied audio-visual learning media and before applying audio-visual learning media is 58.26 to 70.88. So, it can be concluded that audio-visual learning media can affect student learning outcomes in Setia Bhakti Trawas class.